Lithium iron phosphate composite material and preparation method thereof, positive electrode sheet and battery

The conductive network structure constructed through ZIF-67 coating and carbon nanotubes solves the problem of insufficient conductivity of lithium iron phosphate batteries, improves the performance and life of lithium-ion batteries, and reduces costs.

CN118899425BActive Publication Date: 2025-01-10JIANGSU PYLON BATTERY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411377082.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-10
Estimated Expiration
2044-09-30

AI Technical Summary

Technical Problem

Lithium iron phosphate batteries have large internal resistance and high heat generation, resulting in insufficient conductivity. The density decreases after conventional carbon doping, and their volume is huge, making it difficult to apply to actual batteries.

Method used

By dispersing lithium iron phosphate in the reaction solution to be reacted with ZIF-67, ZIF-67 is generated to coat lithium iron phosphate material, and a dense carbon layer is formed in a carbon source atmosphere, and then converted into carbon nanotubes at high temperatures. Conductive network structure.

Benefits of technology

It improves the conductivity and specific surface area of ​​lithium iron phosphate, enhances the shuttle capacity of lithium ions, extends battery life and reduces costs, and avoids side reactions with the electrolyte.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118899425B_ABST
    Figure CN118899425B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of battery materials, and discloses a lithium iron phosphate composite material and a preparation method thereof, a positive electrode sheet and a battery. The preparation method of the lithium iron phosphate composite material comprises: reacting a solution in which cobalt ions are dissolved and lithium iron phosphate is dispersed with a solution in which 2-methylimidazole is dissolved to generate a ZIF-67-coated lithium iron phosphate material; performing carbon deposition on the ZIF-67-coated lithium iron phosphate material; and then placing the carbon deposition product at 750-850° C. to convert the ZIF-67 into a carbon nanotube with cobalt elements distributed inside. The lithium iron phosphate composite material provided by the present invention has excellent conductivity, rate performance and cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery materials, and in particular to a lithium iron phosphate composite material and a preparation method thereof, a positive electrode sheet and a battery. Background Art

[0002] Lithium iron phosphate is a lithium-ion battery electrode material with the chemical formula LiFePO4 (LFP for short), which is mainly used in various lithium-ion batteries. Its theoretical specific capacity is 170 mAh / g, and the actual specific capacity of the product can exceed 140 mAh / g (0.2C, 25°C). Lithium iron phosphate has good lattice stability, and the insertion and extraction of lithium ions have little effect on the lattice, so it has good reversibility. Therefore, under 100% DOD conditions, it can be charged and discharged more than 2000 times. However, conventional lithium iron phosphate batteries prepared from lithium iron phosphate have large internal resistance and high heat generation. Lithium iron phosphate itself has large internal resistance and generates more heat at the same current, especially in large single cells. If the heat dissipation system is inefficient, it will aggravate the heating problem. In order to improve conductivity, people add conductive carbon materials, which significantly reduces the bulk density of the material, making the actual density of general carbon-doped lithium iron phosphate only 1.0~1.2g / cm 3 Such a low stacking density makes the volume-to-capacity of lithium iron phosphate much lower than that of lithium cobalt oxide. The battery made of it will be very large, which not only has no advantages, but also is difficult to apply in practice.

[0003] In the prior art, for example, CN 111224103A, lithium iron phosphate is coated by a sol-gel method and then dried and calcined to obtain a metal ion-doped high-rate mesoporous lithium iron phosphate positive electrode material. Although the electrochemical performance of this positive electrode material is good, there is still room for improvement.

[0004] Zeolitic Imidazolate Frameworks (ZIFs) are a new type of zeolite-like material with a regular microporous network structure formed by the self-assembly of inorganic metal ions and nitrogen-containing multidentate organic ligands through coordination. They are porous crystalline materials. In them, organic imidazolate is cross-linked to the transition metal to form a tetrahedral framework. In recent years, a variety of methods have been developed to synthesize ZIFs of different sizes, morphologies and compositions, such as microfluidics, dry gel method, electrospray, mechanochemical preparation, sonochemical reaction, electrochemical synthesis and other methods. ZIF-67, as a special ZIF material, is formed by the reaction of cobalt nitrate hexahydrate and dimethylimidazole. Due to the special properties and structural characteristics of ZIF-67 material itself, researchers have treated it under different conditions in recent years, making it show superior properties in batteries, superelectric and electrocatalysis. However, due to its inherent microporous characteristics, the structure is prone to collapse under high-temperature calcination, affecting the mass transfer rate of ions, thereby reducing its catalytic activity and electrochemical performance.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] The purpose of the present invention is to provide a lithium iron phosphate composite material and a preparation method thereof, a positive electrode sheet and a battery, aiming to provide a lithium iron phosphate composite material with good electrochemical performance.

[0007] The present invention is achieved in that:

[0008] In a first aspect, the present invention provides a method for preparing a lithium iron phosphate composite material, comprising:

[0009] Mixing a first liquid to be reacted and a second liquid to be reacted to obtain a solid-liquid mixture after the reaction, wherein a cobalt salt is dissolved in the first liquid to be reacted, 2-methylimidazole is dissolved in the second liquid to be reacted, and lithium iron phosphate is dispersed in at least one of the first liquid to be reacted and the second liquid to be reacted;

[0010] Extracting solid matter from the solid-liquid mixture to obtain a ZIF-67 coated lithium iron phosphate material;

[0011] Placing the ZIF-67 coated lithium iron phosphate material in a carbon source atmosphere, decomposing the carbon source gas into carbon deposited on the surface of the ZIF-67 coated lithium iron phosphate material, and obtaining an intermediate material coated with a dense carbon layer;

[0012] The intermediate material is placed in an inert atmosphere at 750-850° C. to convert the ZIF-67 in the intermediate material into carbon nanotubes with cobalt elements distributed inside, thereby forming a conductive network structure in which some carbon nanotubes are inserted into the dense carbon layer on the surface of the lithium iron phosphate.

[0013] In an optional embodiment, the method further includes at least one of the following features (1) to (14):

[0014] (1) In the ZIF-67 coated lithium iron phosphate material, the mass ratio of ZIF-67 to lithium iron phosphate is 0.01-0.2:1.

[0015] (2) The mass ratio of the dense carbon layer to the lithium iron phosphate in the intermediate material is 0.01-0.2:1;

[0016] (3) The carbon source gas is a hydrocarbon organic gas;

[0017] (4) The concentration of the cobalt salt in the first reaction solution is 0.001-0.1 mol / L;

[0018] (5) The concentration of 2-methylimidazole cobalt in the second reaction solution is 0.001-0.1 mol / L;

[0019] (6) The inert atmosphere is an argon atmosphere, or a mixed atmosphere of argon and hydrogen;

[0020] (7) The lithium iron phosphate is dispersed in the first reaction liquid, and the first reaction liquid and the second reaction liquid are mixed and reacted in the following manner:

[0021] Under constant stirring, adding the second reaction liquid to the first reaction liquid;

[0022] (8) The cobalt salt is at least one of cobalt nitrate, cobalt sulfate and cobalt carbonate;

[0023] (9) The method of extracting the solid substance from the solid-liquid mixture includes: firstly performing solid-liquid separation, then centrifugally washing the obtained solid with water and methanol for 2 to 3 times, and then vacuum drying;

[0024] (10) The carbon source gas is methane, and the temperature for decomposing the carbon source gas into carbon is 550-650° C., and the decomposition time is 2-4 hours;

[0025] (11) placing the intermediate material at 750~850℃ for 2~4h;

[0026] (12) The lithium iron phosphate is dispersed in the first reaction solution, and the preparation method of the first reaction solution includes:

[0027] The cobalt salt solution and lithium iron phosphate were mixed and placed in an ultrasonic cell crusher for crushing, the crushing power was set to 70-100%, and the crushing time was 1-2 hours;

[0028] (13) The reaction time of the first reaction liquid and the second reaction liquid is 20 to 26 hours;

[0029] (14) The particle size of the lithium iron phosphate dispersed in the first reaction liquid and / or the second reaction liquid is 400 nm to 1 μm.

[0030] In an optional embodiment, a surfactant is also dispersed in the first liquid to be reacted and / or the second liquid to be reacted.

[0031] In an optional embodiment, the surfactant is selected from at least one of octadecyltrimethylammonium bromide, dodecyltrimethylammonium chloride, dodecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, sodium dodecyl sulfate and sodium alkylbenzene sulfonate.

[0032] In an optional embodiment, the solvent in the first liquid to be reacted and / or the second liquid to be reacted is alcohol.

[0033] In an alternative embodiment, the alcohol is at least one of methanol and ethanol.

[0034] In a second aspect, the present invention provides a lithium iron phosphate composite material, which is prepared by the preparation method of any one of the aforementioned embodiments.

[0035] In a third aspect, the present invention provides a positive electrode sheet, the active component of which includes the lithium iron phosphate composite material as described in the above embodiment.

[0036] In a fourth aspect, the present invention provides a battery, comprising the positive electrode sheet as described in the aforementioned embodiment.

[0037] The present invention has the following beneficial effects:

[0038] The preparation method provided by the embodiment of the present invention can make the ZIF-67 generated by the reaction uniformly coated on the surface of lithium iron phosphate by dispersing lithium iron phosphate in the reaction liquid, making the first reaction liquid and the second reaction liquid mixed and reacted; by cracking the carbon source, a dense carbon layer is deposited outside the lithium iron phosphate particles, and part of the material in the ZIF-67-coated lithium iron phosphate material is carbonized, and then sintered at high temperature to completely transform ZIF-67 into carbon nanotubes. The prepared lithium iron phosphate composite material has uniform morphology, good conductivity, high specific surface area and large pore volume, which can accelerate the shuttle of lithium ions, and the CNTs (carbon nanotubes) formed after the carbonization of ZIF-67 not only increase the conductivity of the material, but also provide a transmission channel for electrons and lithium ions. The CNTs formed after the carbonization of ZIF-67 are different from ordinary carbon nanotubes, and cobalt elements are distributed inside its structure. The presence of Co can increase the capacity of lithium-ion batteries, improve battery life and stabilize battery performance. Therefore, the material has a good prospect in lithium-ion batteries, and has excellent performance even without adding a conductive agent in the positive electrode formulation, significantly reducing the cost of raw materials. In addition, the preparation method provided by the present invention is also characterized by simple operation, easy availability of raw materials, and low cost.

[0039] The lithium iron phosphate composite material provided by the embodiment of the present invention can improve the conductivity of lithium iron phosphate on the one hand, and prevent the side reaction of lithium iron phosphate in contact with the electrolyte on the other hand by coating the dense carbon layer on the surface of lithium iron phosphate; the coating of the conductive network structure constructed by carbon nanotubes can increase the conductivity, so that the lithium iron phosphate composite material has a higher specific surface area and large pore volume, and provides a channel for the transmission of lithium ions, thereby accelerating the shuttle of ions, and the cobalt element distributed in the carbon nanotubes can increase the capacity of the lithium ion battery, improve the battery life and stabilize the battery performance, and a part of the carbon nanotubes in the conductive network structure is inserted in the dense carbon layer, so that the combination of the conductive network structure and the dense carbon layer has a higher stability. Therefore, the lithium iron phosphate composite material provided by the present invention has excellent electrochemical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0041] Figure 1 This is a scanning electron microscope image of the CNTs-Co@LiFePO4 composite material prepared in Example 1 of the present invention;

[0042] Figure 2 This is a transmission electron microscope image of the CNTs-Co@LiFePO4 composite material prepared in Example 1 of the present invention;

[0043] Figure 3 This is an EDX image of the CNTs-Co@LiFePO4 composite material prepared in Example 1 of the present invention;

[0044] Figure 4 Impedance diagrams of the positive electrode materials prepared in Example 1 and Comparative Example 1 in CR2032 button-type half-cells;

[0045] Figure 5 The rate curves of the positive electrode materials prepared in Example 1 and Comparative Example 1 at different current densities in a CR2032 button-type half-cell;

[0046] Figure 6 The following is a normal temperature cycle curve of the positive electrode materials prepared in Example 1 and Comparative Example 1 without and with a conductive agent in a CR2032 button half-cell. DETAILED DESCRIPTION

[0047] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.

[0048] The lithium iron phosphate composite material and its preparation method, positive electrode sheet and battery provided in the embodiments of the present invention are described in detail below.

[0049] The method for preparing the lithium iron phosphate composite material provided by the embodiment of the present invention comprises:

[0050] The first liquid to be reacted and the second liquid to be reacted are mixed and reacted to obtain a solid-liquid mixture after the reaction is completed, wherein a cobalt salt is dissolved in the first liquid to be reacted, 2-methylimidazole is dissolved in the second liquid to be reacted, and lithium iron phosphate is dispersed in at least one of the first liquid to be reacted and the second liquid to be reacted;

[0051] Extracting solid matter from the solid-liquid mixture to obtain ZIF-67 coated lithium iron phosphate material;

[0052] Placing the ZIF-67 coated lithium iron phosphate material in a carbon source atmosphere, decomposing the carbon source gas into carbon that is deposited on the surface of the ZIF-67 coated lithium iron phosphate material, and obtaining an intermediate material coated with a dense carbon layer;

[0053] The intermediate material is placed in an inert atmosphere at 750-850°C (e.g., 750°C, 800°C, or 580°C) to convert the ZIF-67 in the intermediate material into carbon nanotubes with cobalt elements distributed inside, thereby forming a conductive network structure on the surface of the lithium iron phosphate in which some carbon nanotubes are inserted into a dense carbon layer.

[0054] The preparation method provided by the present invention can make the ZIF-67 generated by the reaction uniformly coated on the surface of the lithium iron phosphate by dispersing lithium iron phosphate in the liquid to be reacted, and making the first liquid to be reacted and the second liquid to be reacted mixed and reacted; by cracking the carbon source, a dense carbon layer is deposited outside the lithium iron phosphate particles, and part of the material in the ZIF-67-coated lithium iron phosphate material is carbonized, and then sintered at high temperature, so that the ZIF-67 is completely converted into carbon nanotubes. The prepared lithium iron phosphate composite material has uniform morphology, good conductivity, high specific surface area and large pore volume, which can accelerate the shuttle of lithium ions, and the CNTs (carbon nanotubes) formed after the carbonization of ZIF-67 not only increase the conductivity of the material, but also provide a transmission channel for electrons and lithium ions, and the CNTs formed after the carbonization of ZIF-67 are different from ordinary carbon nanotubes, and the cobalt element is distributed inside its structure, and the presence of Co can increase the capacity of lithium ion batteries, improve battery life and stabilize battery performance. Therefore, the material has a good prospect in lithium-ion batteries, and has excellent performance even without adding a conductive agent in the positive electrode formulation, significantly reducing the cost of raw materials. In addition, the preparation method provided by the present invention is also characterized by simple operation, easy availability of raw materials, and low cost.

[0055] The preparation method is specifically as follows:

[0056] S1. Preparation of the first reaction solution

[0057] Adding a cobalt salt to the first solvent and stirring to completely dissolve the cobalt salt to obtain a cobalt salt solution having a concentration of 0.001 to 0.1 mol / L (e.g., 0.001 mol / L, 0.005 mol / L, 0.01 mol / L, 0.05 mol / L, 0.08 mol / L or 0.1 mol / L);

[0058] According to the solid-liquid ratio of 0.1~1g: 50~500mL (for example, 0.1g:500mL, 0.5:500mL, 1:500mL, 0.1:50mL, 0.5g:50mL, 1g:50mL, 0.1g:100mL, 0.5g:100mL, 1g:100mL), the lithium iron phosphate and the cobalt salt solution are evenly mixed and transferred into an ultrasonic cell pulverizer, the power of which is set to 70~100% (for example, 70%, 80%, 90% or 100%), the lithium iron phosphate therein is pulverized, a surfactant is added during the pulverization process, and the pulverization is completed after 1~2 hours to obtain a first reaction liquid.

[0059] Optionally, the ratio of the amount of surfactant added to the cobalt salt solution is 0.1-1 g: 50-500 mL (e.g., 0.1 g: 500 mL, 0.5: 500 mL, 1: 500 mL, 0.1: 50 mL, 0.5 g: 50 mL, 1 g: 50 mL, 0.1 g: 100 mL, 0.5 g: 100 mL, 1 g: 100 mL). The addition of an appropriate amount of surfactant helps to disperse the lithium iron phosphate more evenly in the solution.

[0060] Optionally, the surfactant is selected from at least one of octadecyltrimethylammonium bromide, dodecyltrimethylammonium chloride, dodecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, sodium dodecyl sulfate and sodium alkylbenzene sulfonate.

[0061] Optionally, the first solvent is alcohol. Further, the alcohol may be at least one of methanol and ethanol.

[0062] Optionally, the cobalt salt is selected from at least one of cobalt nitrate, cobalt sulfate and cobalt carbonate, preferably cobalt nitrate or a hydrate of cobalt nitrate.

[0063] It should be noted that in this step, the purpose of adding lithium iron phosphate to the cobalt salt solution and then placing it in an ultrasonic cell crusher is to crush the lithium iron phosphate and make the lithium iron phosphate more evenly dispersed in the solution. It is preferably crushed to a particle size of 400 nm to 1 μm to ensure that a lithium iron phosphate composite material with better performance is obtained. If the particle size of the lithium iron phosphate used is not large, it does not need to be placed in an ultrasonic cell crusher for treatment.

[0064] S2. Preparation of the second reaction solution

[0065] 2-methylimidazole is added to the second solvent, and the mixture is stirred to completely dissolve the 2-methylimidazole. A surfactant is then added and stirred to obtain a second reaction solution.

[0066] Optionally, the second solvent is an alcohol. Further, the alcohol may be at least one of methanol and ethanol.

[0067] Optionally, the surfactant is selected from at least one of octadecyltrimethylammonium bromide, dodecyltrimethylammonium chloride, dodecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, sodium dodecyl sulfate and sodium alkylbenzene sulfonate.

[0068] It should be noted that lithium iron phosphate may or may not be added to the second reaction liquid. For example, in some embodiments of the present invention, lithium iron phosphate may not be added to the first reaction liquid but may be added to the second reaction liquid, or may be added to both the first reaction liquid and the second reaction liquid.

[0069] S3. Preparation of ZIF-67 coated lithium iron phosphate material

[0070] The prepared second reaction liquid is slowly added to the lithium iron phosphate mixed methanol solution, and stirring is continued during the process. The reaction is terminated after 20 to 26 hours (for example, 20 hours, 24 hours or 26 hours) to obtain a solid-liquid mixture.

[0071] The obtained solid-liquid mixture is subjected to solid-liquid separation, and then the obtained solid is centrifugally washed with water and methanol for 2 to 3 times, and then the object is placed at 50 to 70°C (for example, 50°C, 60°C or 70°C) and vacuum dried for 10 to 14 hours (for example, 10 hours, 12 hours or 14 hours) to obtain ZIF-67 coated lithium iron phosphate material.

[0072] Optionally, to ensure that the prepared lithium iron phosphate composite material has better performance, the ratio of ZIF-67 to lithium iron phosphate in the prepared ZIF-67 coated lithium iron phosphate material is 0.01~0.2:1 (for example, 0.01:1, 0.05:1, 0.1:1 or 0.2:1).

[0073] S4. Carbon deposition

[0074] The ZIF-67 coated lithium iron phosphate material is placed in a carbon source atmosphere, and the ambient temperature is increased to decompose the carbon source gas into carbon that is deposited on the surface of the ZIF-67 coated lithium iron phosphate material to obtain an intermediate material.

[0075] Optionally, the carbon source gas is a hydrocarbon organic gas.

[0076] Furthermore, the carbon source gas is methane, the ambient temperature is 550-650°C (eg, 550°C, 600°C, or 650°C), and the decomposition time is 2-4h (eg, 2h, 3h, or 4h).

[0077] It should be noted that the ambient temperature and time to be set will be different depending on the selected carbon source gas, and the specific decomposition temperature and time need to be determined according to the selected carbon source gas.

[0078] Optionally, the ratio of the dense carbon layer to the lithium iron phosphate in the prepared intermediate material is 0.01-0.2:1 (eg, 0.01:1, 0.05:1, 0.1:1 or 0.2:1).

[0079] S5. Sintering

[0080] The prepared intermediate material is transferred to a tube furnace, and in an inert atmosphere, the temperature is increased to 750-850°C (e.g., 750°C, 800°C, or 850°C) at a heating rate of 1-5°C / min (e.g., 1°C / min, 3°C / min, or 5°C / min) and maintained for 2.5-5h (e.g., 2.5h, 4h, or 5h). After the high-temperature reaction is completed, a carbon nanotube-cobalt-carbon-coated lithium iron phosphate composite material is obtained.

[0081] In different atmospheres, ZIF-67 will decompose into different substances at high temperature, and its high temperature carbonization products have good conductivity. This application makes ZIF-67 carbonized at high temperature in an inert atmosphere to transform it into carbon nanotubes to provide a special pathway for lithium ion transmission. Therefore, the high temperature products of ZIF-67 provide good conductivity for lithium iron phosphate.

[0082] The lithium iron phosphate composite material provided by the embodiment of the present invention is prepared by the preparation method provided by the embodiment of the present invention.

[0083] Specifically, the lithium iron phosphate composite material comprises: a lithium iron phosphate core and a composite carbon layer coated on the surface of the lithium iron phosphate core;

[0084] The composite carbon layer includes a dense carbon layer and a conductive network structure constructed by carbon nanotubes, wherein cobalt elements are distributed in the carbon nanotubes;

[0085] A portion of the carbon nanotubes in the conductive network structure are inserted into the dense carbon layer.

[0086] The lithium iron phosphate composite material provided by the present invention can improve the conductivity of lithium iron phosphate on the one hand, and prevent the side reaction of lithium iron phosphate in contact with electrolyte on the other hand by coating the dense carbon layer on the surface of lithium iron phosphate; the coating layer of the conductive network structure constructed by carbon nanotubes can increase the conductivity, so that the lithium iron phosphate composite material has a higher specific surface area and large pore volume, provides a channel for the transmission of lithium ions, thereby accelerating the shuttle of ions, and the cobalt element distributed in the carbon nanotubes can increase the capacity of lithium ion batteries, improve battery life and stabilize battery performance, and a part of the carbon nanotubes in the conductive network structure is inserted in the dense carbon layer, so that the combination of the conductive network structure and the dense carbon layer has a higher stability. Therefore, the lithium iron phosphate composite material provided by the present invention has excellent electrochemical properties.

[0087] Optionally, to ensure that the lithium iron phosphate composite material has better electrochemical properties, the mass ratio of cobalt element to carbon nanotubes is 0.01~0.2:1 (for example, 0.01:1, 0.05:1, 0.1:1 or 0.2:1); and / or, the mass ratio of the dense carbon layer to the lithium iron phosphate core is 0.01~0.2:1 (for example, 0.01:1, 0.05:1, 0.1:1 or 0.2:1); and / or, the mass ratio of the conductive network structure to the lithium iron phosphate core is 0.01~0.2:1 (for example, 0.01:1, 0.05:1, 0.1:1 or 0.2:1).

[0088] The positive electrode sheet provided in the embodiment of the present invention has an active component comprising the lithium iron phosphate composite material provided in the embodiment of the present invention, or the lithium iron phosphate composite material prepared by the preparation method provided in the embodiment of the present invention.

[0089] The battery provided by the embodiment of the present invention includes the positive electrode sheet provided by the embodiment of the present invention.

[0090] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.

[0091] The lithium iron phosphate used in the following examples was purchased from Sinopharm Reagent, with the code TL0386100G; the lithium iron phosphate used in the comparative example was purchased from Shenzhen Defang Nanotechnology Co., Ltd., with the model number DY-1.

[0092] The commercial sources of carbon nanotubes used in Comparative Example 3 are shown in Table 1:

[0093] Table 1 Commercial sources of carbon nanotubes

[0094]

[0095] The method for detecting the content of each element in the product obtained in the following examples is as follows. Since the test method belongs to the prior art, only a brief description is given here:

[0096] (1) Carbon material content detection

[0097] 1. Full spectrum scanning method:

[0098] Mix a sample of a substance with a certain amount of oxygen and burn it at high temperature. The CO2 produced will cause the luminescent substance in the air to undergo a chemiluminescent reaction. Then use a spectrometer to analyze the light emitted by the luminescent substance and calculate the carbon content in the substance.

[0099] 2. After step 4) of each embodiment is completed, the mass increment is measured. The mass increment of the material before and after cracking is the mass of the dense carbon layer. The mass of the carbon nanotube is the carbon content measured by the full spectrum scanning method minus the mass increment of the dense carbon layer.

[0100] (2) Detection of metal element content

[0101] ICP elemental analysis method:

[0102] 1. Sample preparation: Pre-treat the sample appropriately by using aqua regia for digestion, dilution or extraction.

[0103] 2. Preparation of standard solutions: For quantitative analysis, a series of standard solutions containing known concentrations of target metal elements need to be prepared to draw a calibration curve.

[0104] 3. Instrument calibration: Use standard solution to calibrate the instrument to ensure the accuracy of the test results.

[0105] 4. Sample analysis: The processed samples are injected into the ICP instrument. The high-temperature plasma generated by the instrument ionizes the metal elements in the sample and emits a characteristic spectrum. The type and content of the elements are determined by spectral analysis or mass spectrometry.

[0106] 5. Data analysis: Calculate the concentration of each metal element in the sample based on the data collected by the instrument and compare it with the calibration curve.

[0107] Example 1

[0108] This embodiment provides a method for preparing a lithium iron phosphate composite material, specifically:

[0109] 1) Take a 150ml beaker, add 3mmol of cobalt nitrate hexahydrate and 60ml of methanol solution into the beaker, stir to completely dissolve the cobalt nitrate hexahydrate, weigh 300mg of commercial lithium iron phosphate and add it to the mixed solution, stir evenly and transfer it into an ultrasonic cell crusher, set its power to 70%, add 50mg of hexadecyltrimethylammonium bromide during the crushing process, and crush for 1 hour to obtain the first reaction solution;

[0110] 2) Take another 100 ml beaker, add 12 mmol of 2-methylimidazole and 60 ml of methanol solution into the beaker, stir to completely dissolve the 2-methylimidazole cobalt, then add 50 mg of hexadecyltrimethylammonium bromide, stir to dissolve to obtain the second reaction solution for use;

[0111] 3) Slowly add the prepared second reaction liquid to the first reaction liquid, stirring continuously during the process, and the reaction ends after 24 hours. The precipitate is washed three times by centrifugation with water and methanol, and vacuum dried at 60°C for 12 hours to obtain ZIF-67 coated lithium iron phosphate material;

[0112] 4) The ZIF-67 coated lithium iron phosphate material is placed in a methane atmosphere and sintered at 600°C for 3 hours to obtain an intermediate material coated with a dense carbon layer;

[0113] 5) The prepared intermediate material coated with a dense carbon layer was transferred to a tube furnace, heated to 800°C and maintained for 3 hours at a heating rate of 3°C / min under an argon hydrogen atmosphere. After the high temperature reaction, about 324 mg of lithium iron phosphate composite material CNTs-Co@LiFePO4 coated with a dense carbon layer and a carbon nanotube conductive network was obtained, wherein the mass ratio of the dense carbon layer to lithium iron phosphate was about 0.03:1, the mass ratio of the conductive network structure to lithium iron phosphate was about 0.05:1, and the mass ratio of the cobalt element in the conductive network structure to the carbon nanotube was about 0.05:1.

[0114] Example 2

[0115] This embodiment provides a method for preparing a lithium iron phosphate composite material, specifically:

[0116] 1) Take a 150ml beaker, add 1mmol of cobalt nitrate hexahydrate and 60ml of methanol solution into the beaker, stir to completely dissolve the cobalt nitrate hexahydrate, weigh 300mg of commercial lithium iron phosphate and add it to the mixed solution, stir evenly and transfer it into an ultrasonic cell crusher, set its power to 100%, add 10mg of hexadecyltrimethylammonium bromide during the crushing process, and crush for 2 hours to obtain the first reaction solution;

[0117] 2) Take another 100 ml beaker, add 6 mmol of 2-methylimidazole and 60 ml of methanol solution into the beaker, stir to completely dissolve the 2-methylimidazole cobalt, then add 10 mg of hexadecyltrimethylammonium bromide, stir to dissolve to obtain the second reaction solution for use;

[0118] 3) Slowly add the prepared second reaction liquid to the first reaction liquid, stirring continuously during the process, and the reaction ends after 20 hours. The precipitate is washed twice by centrifugation with water and methanol, and vacuum dried at 60° C. for 12 hours to obtain ZIF-67 coated lithium iron phosphate material;

[0119] 4) The ZIF-67 coated lithium iron phosphate material was placed in a methane atmosphere and sintered at 550°C for 4 hours to obtain an intermediate material coated with a dense carbon layer;

[0120] 5) The intermediate material coated with a dense carbon layer prepared above was transferred to a tube furnace, heated to 750°C and maintained for 5 hours at a heating rate of 1°C / min under an argon hydrogen atmosphere. After the high-temperature reaction was completed, about 300 mg of lithium iron phosphate composite material CNTs-Co@LiFePO4 coated with a dense carbon layer and a carbon nanotube conductive network was obtained. The mass ratio of the dense carbon layer to lithium iron phosphate contained therein is about 0.03:1, the mass ratio of the conductive network structure to lithium iron phosphate is about 0.02:1, and the mass ratio of the cobalt element in the conductive network structure to the carbon nanotube is about 0.01:1.

[0121] Example 3

[0122] This embodiment provides a method for preparing a lithium iron phosphate composite material, specifically:

[0123] 1) Take a 150ml beaker, add 100mmol of cobalt nitrate hexahydrate and 60ml of methanol solution into the beaker, stir to completely dissolve the cobalt nitrate hexahydrate, weigh 300mg of commercial lithium iron phosphate and add it to the mixed solution, stir evenly and transfer it into an ultrasonic cell crusher, set its power to 80%, add 100mg of hexadecyltrimethylammonium bromide during the crushing process, and crush for 2 hours to obtain the first reaction solution;

[0124] 2) Take another 100 ml beaker, add 100 mmol of 2-methylimidazole and 60 ml of methanol solution into the beaker, stir to completely dissolve the 2-methylimidazole cobalt, then add 100 mg of hexadecyltrimethylammonium bromide, stir to dissolve to obtain the second reaction solution for use;

[0125] 3) The prepared second reaction liquid was slowly added to the first reaction liquid, and continuous stirring was required during the process. The reaction was terminated after 26 hours. The precipitate was centrifuged and washed twice with water and methanol, and vacuum dried at 60° C. for 12 hours to obtain ZIF-67 coated lithium iron phosphate material;

[0126] 4) The ZIF-67 coated lithium iron phosphate material is placed in a methane atmosphere and sintered at 650°C for 2 hours to obtain an intermediate material coated with a dense carbon layer;

[0127] 5) The intermediate material coated with a dense carbon layer prepared above was transferred to a tube furnace, heated to 850°C and maintained for 2.5 hours at a heating rate of 5°C / min under an argon hydrogen atmosphere. After the high-temperature reaction was completed, about 300 mg of lithium iron phosphate composite material CNTs-Co@LiFePO4 coated with a dense carbon layer and a carbon nanotube conductive network was obtained. The mass ratio of the dense carbon layer to lithium iron phosphate contained therein is about 0.03:1, the mass ratio of the conductive network structure to lithium iron phosphate is about 0.16:1, and the mass ratio of cobalt element to carbon nanotubes in the conductive network structure is about 0.2:1.

[0128] Example 4

[0129] This embodiment is basically the same as Embodiment 1, except that: by adjusting the ratio of the added raw materials, the mass ratio of the dense carbon layer to the lithium iron phosphate in the prepared lithium iron phosphate composite material is approximately 0.01:1, the mass ratio of the conductive network structure to the lithium iron phosphate is approximately 0.01:1, and the mass ratio of the cobalt element to the carbon nanotubes in the conductive network structure is approximately 0.01:1.

[0130] The specific operation method is:

[0131] 1) Take a 150ml beaker, add 1mmol of cobalt nitrate hexahydrate and 60ml of methanol solution into the beaker, stir to completely dissolve the cobalt nitrate hexahydrate, weigh 300mg of commercial lithium iron phosphate and add it to the mixed solution, stir evenly and transfer it into an ultrasonic cell crusher, set its power to 70%, add 50mg of hexadecyltrimethylammonium bromide during the crushing process, and crush for 1 hour to obtain the first reaction solution;

[0132] 2) Take another 100 ml beaker, add 2 mmol of 2-methylimidazole and 60 ml of methanol solution into the beaker, stir to completely dissolve the 2-methylimidazole cobalt, then add 50 mg of hexadecyltrimethylammonium bromide, stir to dissolve to obtain the second reaction solution for use;

[0133] 3) Slowly add the prepared second reaction liquid to the first reaction liquid, stirring continuously during the process, and the reaction ends after 24 hours. The precipitate is washed three times by centrifugation with water and methanol, and vacuum dried at 60°C for 12 hours to obtain ZIF-67 coated lithium iron phosphate material;

[0134] 4) The ZIF-67 coated lithium iron phosphate material is placed in a methane atmosphere and sintered at 600°C for 1 hour to obtain an intermediate material coated with a dense carbon layer;

[0135] 5) The intermediate material coated with a dense carbon layer prepared above was transferred to a tube furnace, and heated to 800°C and maintained for 3 hours at a heating rate of 3°C / min under an argon-hydrogen atmosphere. After the high-temperature reaction was completed, about 324 mg of lithium iron phosphate composite material CNTs-Co@LiFePO4 coated with a dense carbon layer and a carbon nanotube conductive network was obtained.

[0136] Example 5

[0137] This embodiment is basically the same as Embodiment 1, except that, by adjusting the ratio of the added raw materials, the mass ratio of the dense carbon layer to the lithium iron phosphate in the prepared lithium iron phosphate composite material is approximately 0.2:1, the mass ratio of the conductive network structure to the lithium iron phosphate is approximately 0.2:1, and the mass ratio of the cobalt element in the conductive network structure to the carbon nanotubes is approximately 0.2:1.

[0138] 1) Take a 150ml beaker, add 100mmol of cobalt nitrate hexahydrate and 60ml of methanol solution into the beaker, stir to completely dissolve the cobalt nitrate hexahydrate, weigh 300mg of commercial lithium iron phosphate and add it to the mixed solution, stir evenly and transfer it into an ultrasonic cell crusher, set its power to 70%, add 50mg of hexadecyltrimethylammonium bromide during the crushing process, and crush for 1 hour to obtain the first reaction solution;

[0139] 2) Take another 100 ml beaker, add 150 mmol of 2-methylimidazole and 60 ml of methanol solution into the beaker, stir to completely dissolve the 2-methylimidazole cobalt, then add 50 mg of hexadecyltrimethylammonium bromide, stir to dissolve to obtain the second reaction solution for use;

[0140] 3) Slowly add the prepared second reaction liquid to the first reaction liquid, stirring is required during the process, and the reaction is terminated after 24 hours. The precipitate is washed three times by centrifugation with water and methanol, and vacuum dried at 60° C. for 12 hours to obtain ZIF-67 coated lithium iron phosphate material;

[0141] 4) The ZIF-67 coated lithium iron phosphate material is placed in a methane atmosphere and sintered at 600°C for 12 hours to obtain an intermediate material coated with a dense carbon layer;

[0142] 5) The intermediate material coated with a dense carbon layer prepared above was transferred to a tube furnace, and heated to 800°C and maintained for 3 hours at a heating rate of 3°C / min under an argon-hydrogen atmosphere. After the high-temperature reaction was completed, about 324 mg of lithium iron phosphate composite material CNTs-Co@LiFePO4 coated with a dense carbon layer and a carbon nanotube conductive network was obtained.

[0143] Comparative Example 1

[0144] 1) Dissolve 2.50 kg of ferric chloride, 0.50 kg of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer (P123), 1.57 kg of phosphoric acid, 1.16 kg of lithium carbonate, 0.1 kg of manganese chloride and 0.75 kg of terephthalic acid in a mixture of 7 kg of pure water and 7 kg of N,N-dimethylformamide, adjust the pH value to 1.5 with hydrochloric acid, and stir evenly;

[0145] 2) The solution obtained in step (1) is stirred at room temperature for 1 hour, and then heated and stirred at 80° C. until a sol is formed, in which manganese ions are complexed with terephthalic acid to obtain a metal organic framework material Mn-MOFs, which is uniformly dispersed in the sol;

[0146] 3) transferring the sol obtained in step (2) to an oven, drying and aging at 100° C. for 24 h to obtain a dry gel;

[0147] 4) transferring the dry gel obtained in step (3) to an atmosphere furnace and sintering at 700° C. for 10 h under nitrogen protection to obtain a sintered material;

[0148] 5) The sintered material obtained in step (4) is cooled and passed through a 200-mesh sieve to obtain a lithium iron phosphate positive electrode material.

[0149] Comparative Example 2

[0150] This comparative example is basically the same as Example 1, except that: ZIF-67 is not coated, 300 mg of lithium iron phosphate is directly placed in a methane atmosphere, sintered at 600°C, and reacted for 3 hours. After the reaction, about 320 mg of lithium iron sulfate material coated with a dense carbon layer is obtained.

[0151] Comparative Example 3

[0152] This comparative example is basically the same as Example 1, except that: instead of coating ZIF-67, 300 mg of lithium iron phosphate, 15 mg of carbon nanotubes and 0.75 mg of metal cobalt are directly ball-milled and mixed, then placed in a methane atmosphere, sintered at 600°C, reacted for 3 hours, and after the reaction, about 324 mg of an intermediate material coated with a dense carbon layer is obtained.

[0153] It should be noted that, in the above-mentioned embodiments and comparative examples, the quality of the products actually produced is less than the expected theoretical value due to losses, burning and other reasons during the transfer process, and the ratios of the various components in the final products are obtained through subsequent testing.

[0154] Experimental example

[0155] The positive electrode materials prepared in each embodiment and comparative example were assembled into batteries, and their electrochemical performance was tested. The specific method of assembling the batteries is as follows:

[0156] (a) No conductive agent added

[0157] The positive electrode material (90 mg) prepared in each embodiment and comparative example was weighed, ground evenly in a mortar, and then a binder (the binder was PVDF, about 10 mg) was added. After mixing evenly, the mixture was coated on an aluminum foil and dried in a vacuum drying oven. After drying, the mixture was cut into pieces using a cutting machine, and the mass of each piece was weighed and recorded. Then, the pieces were assembled into a CR2032 battery in a glove box, and their performance was further tested on an electrochemical workstation and a battery testing system.

[0158] (b) Adding conductive agent

[0159] The positive electrode material (80 mg) and the conductive agent carbon black (10 mg) prepared in each embodiment and comparative example were weighed, ground evenly in a mortar, and then a binder (the binder was PVDF, about 10 mg) was added. After mixing evenly, the mixture was coated on an aluminum foil and dried in a vacuum drying oven. After drying, the mixture was cut into pieces with a cutting machine, and the mass of each piece was weighed and recorded. Then, the pieces were assembled into button-type half-cells of model CR2032 in a glove box, and their performance was further tested on an electrochemical workstation and a battery testing system.

[0160] (c) Product verification

[0161] The conductivity of the powder of the positive electrode material prepared in each embodiment and comparative example, and the conductivity of the positive electrode sheet prepared with and without a conductive agent were tested. The test results are shown in Table 2 and Table 3.

[0162] The SEM image of the lithium iron phosphate composite material prepared in Example 1 is as follows: Figure 1 As shown;

[0163] The transmission electron microscope image of the lithium iron phosphate composite material prepared in Example 1 is as follows: Figure 2 As shown;

[0164] The EDX image of the lithium iron phosphate composite material prepared in Example 1 is as follows: Figure 3 As shown;

[0165] The impedance of the button cells prepared in Example 1 and Comparative Example 1 was tested. Figure 4 As shown;

[0166] The rate curves of the button cells prepared in Example 1 and Comparative Example 1 at different current densities are as follows: Figure 5 As shown;

[0167] The cycle performance of the button cells prepared in Example 1 and Comparative Example 1 was tested. Figure 6 shown.

[0168] Table 2 Powder conductivity

[0169]

[0170] Table 3 Electrode conductivity

[0171]

[0172] It can be seen from Table 2 and Table 3 that the positive electrode materials prepared in various embodiments of the present invention have higher electrical conductivity, and the prepared positive electrode sheets also have higher electrical conductivity, which is significantly higher than that of various comparative examples.

[0173] from Figure 1 It can be seen that the carbon nanotubes-cobalt formed after high-temperature carbonization of ZIF-67 are uniformly attached to the surface of lithium iron phosphate. Figure 2 It can be seen that lithium iron phosphate is the "core" and carbon nanotube-cobalt is the "shell" to form a uniform core-shell structure. Figure 3 It can be seen that the prepared lithium iron phosphate composite material contains uniformly distributed Co element, Fe element and C element.

[0174] Figure 4 This is the impedance measured in a CR2032 button cell when the carbon nanotube-cobalt-coated lithium iron phosphate composite material prepared in Example 1 of the present invention is used as the positive electrode material of a lithium-ion battery without a conductive agent. It can be clearly seen from the figure that the lithium iron phosphate composite material prepared in the embodiment of the present invention has better conductivity than the lithium iron phosphate positive electrode material prepared in Comparative Example 1.

[0175] Figure 5 The rate curves at different current densities measured in a CR2032 button half-cell using the carbon nanotube-cobalt-coated lithium iron phosphate composite material prepared in Example 1 of the present invention as a positive electrode material for a lithium-ion battery without using a conductive agent. Compared with the positive electrode material of Comparative Example 1, the carbon nanotube-cobalt-coated lithium iron phosphate composite material of the present application as a positive electrode material for a lithium-ion battery exhibits excellent rate performance at different current densities.

[0176] Figure 6 The cycle performance of CR2032 button-type half-cells assembled with the positive electrode materials prepared in Example 1 and Comparative Example 1 as the positive electrode main material, with and without conductive agents. Figure 6 It can be seen that the lithium iron phosphate composite materials prepared in various embodiments of the present invention have better conductivity than various comparative examples, and have better cycle performance than comparative example 1 even in the absence of a conductive agent.

[0177] In summary, the lithium iron phosphate composite material provided by the embodiment of the present invention can improve the conductivity of lithium iron phosphate on the one hand, and prevent the side reaction of lithium iron phosphate in contact with the electrolyte on the other hand by coating the dense carbon layer on the surface of lithium iron phosphate; the coating of the conductive network structure constructed by carbon nanotubes can increase the conductivity, so that the lithium iron phosphate composite material has a higher specific surface area and large pore volume, and provides a channel for the transmission of lithium ions, thereby accelerating the shuttle of ions, and the cobalt element distributed in the carbon nanotubes can increase the capacity of the lithium ion battery, improve the battery life and stabilize the battery performance, and a part of the carbon nanotubes in the conductive network structure is inserted in the dense carbon layer, so that the combination of the conductive network structure and the dense carbon layer has a higher stability. Therefore, the lithium iron phosphate composite material provided by the present invention has excellent electrochemical properties.

[0178] The preparation method provided by the embodiment of the present invention can make the ZIF-67 generated by the reaction uniformly coated on the surface of lithium iron phosphate by dispersing lithium iron phosphate in the reaction liquid, making the first reaction liquid and the second reaction liquid mixed and reacted; by cracking the carbon source, a dense carbon layer is deposited outside the lithium iron phosphate particles, and part of the material in the ZIF-67-coated lithium iron phosphate material is carbonized, and then sintered at high temperature to completely transform ZIF-67 into carbon nanotubes. The prepared lithium iron phosphate composite material has uniform morphology, good conductivity, high specific surface area and large pore volume, which can accelerate the shuttle of lithium ions, and the CNTs (carbon nanotubes) formed after the carbonization of ZIF-67 not only increase the conductivity of the material, but also provide a transmission channel for electrons and lithium ions. The CNTs formed after the carbonization of ZIF-67 are different from ordinary carbon nanotubes, and cobalt elements are distributed inside its structure. The presence of Co can increase the capacity of lithium-ion batteries, improve battery life and stabilize battery performance. Therefore, the material has a good prospect in lithium-ion batteries, and has excellent performance even without adding a conductive agent in the positive electrode formulation, significantly reducing the cost of raw materials. In addition, the preparation method provided by the present invention is also characterized by simple operation, easy availability of raw materials, and low cost.

[0179] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a lithium iron phosphate composite material, characterized in that: include: Mixing a first liquid to be reacted and a second liquid to be reacted to obtain a solid-liquid mixture after the reaction, wherein a cobalt salt is dissolved in the first liquid to be reacted, 2-methylimidazole is dissolved in the second liquid to be reacted, and lithium iron phosphate is dispersed in at least one of the first liquid to be reacted and the second liquid to be reacted; Extracting solid matter from the solid-liquid mixture to obtain a ZIF-67 coated lithium iron phosphate material; Placing the ZIF-67 coated lithium iron phosphate material in a carbon source atmosphere, decomposing the carbon source gas into carbon deposited on the surface of the ZIF-67 coated lithium iron phosphate material, and obtaining an intermediate material coated with a dense carbon layer; The intermediate material is placed in an inert atmosphere at 750-850° C. to convert the ZIF-67 in the intermediate material into carbon nanotubes with cobalt elements distributed inside, thereby forming a conductive network structure in which some carbon nanotubes are inserted into the dense carbon layer on the surface of the lithium iron phosphate.

2. The preparation method according to claim 1, characterized in that: Also includes at least one of the following features (1) to (14): (1) In the ZIF-67 coated lithium iron phosphate material, the mass ratio of ZIF-67 to lithium iron phosphate is 0.01-0.2:1; (2) The mass ratio of the dense carbon layer to the lithium iron phosphate in the intermediate material is 0.01-0.2:1; (3) The carbon source gas is a hydrocarbon organic gas; (4) The concentration of the cobalt salt in the first reaction solution is 0.001-0.1 mol / L; (5) The concentration of 2-methylimidazole cobalt in the second reaction solution is 0.001-0.1 mol / L; (6) The inert atmosphere is an argon atmosphere, or a mixed atmosphere of argon and hydrogen; (7) The lithium iron phosphate is dispersed in the first reaction liquid, and the first reaction liquid and the second reaction liquid are mixed and reacted in the following manner: Adding the second reaction liquid to the first reaction liquid under continuous stirring; (8) The cobalt salt is at least one of cobalt nitrate, cobalt sulfate and cobalt carbonate; (9) The method of extracting the solid substance from the solid-liquid mixture includes: firstly performing solid-liquid separation, then centrifugally washing the obtained solid with water and methanol for 2 to 3 times, and then vacuum drying; (10) The carbon source gas is methane, and the temperature for decomposing the carbon source gas into carbon is 550-650° C., and the decomposition time is 2-4 hours; (11) placing the intermediate material at 750~850℃ for 2~4h; (12) The lithium iron phosphate is dispersed in the first reaction solution, and the preparation method of the first reaction solution includes: The cobalt salt solution and lithium iron phosphate were mixed and placed in an ultrasonic cell crusher for crushing, the crushing power was set to 70-100%, and the crushing time was 1-2 hours; (13) The reaction time of the first reaction liquid and the second reaction liquid is 20 to 26 hours; (14) The particle size of the lithium iron phosphate dispersed in the first reaction liquid and / or the second reaction liquid is 400 nm to 1 μm.

3. The preparation method according to claim 1, characterized in that: A surfactant is also dispersed in the first liquid to be reacted and / or the second liquid to be reacted.

4. The preparation method according to claim 3, characterized in that: The surfactant is selected from at least one of octadecyltrimethylammonium bromide, dodecyltrimethylammonium chloride, dodecyltrimethylammonium bromide, octadecyltrimethylammonium chloride, sodium dodecyl sulfate and sodium alkylbenzene sulfonate.

5. The preparation method according to claim 1, characterized in that: The solvent in the first liquid to be reacted and / or the second liquid to be reacted is alcohol.

6. The preparation method according to claim 5, characterized in that: The alcohol is at least one of methanol and ethanol.

7. A lithium iron phosphate composite material, characterized in that: The method is prepared according to any one of claims 1 to 6.

8. A positive electrode sheet, characterized in that: The active component thereof includes the lithium iron phosphate composite material as claimed in claim 7.

9. A battery, characterized in that: Comprising the positive electrode sheet as claimed in claim 8.

Citation Information

Patent Citations

  • Preparation method of metal ion doped high-rate mesoporous lithium iron phosphate positive electrode material

    CN111224103A

  • Modified lithium iron phosphate material, preparation method and application thereof

    CN108199041A

  • Lithium ion battery cathode material and preparation method thereof

    CN110085828A